Challenges in coupling atmospheric electricity with biological systems - Ellard R. Hunting; James Matthews; Pablo Fernández de Arróyabe Hernáez; Sam J. England; Konstantinos Kourtidis; Kuang Koh; Keri Nicoll; R. Giles Harrison; Konstantine Manser; Colin Price; Snezana Dragovic; Michal Cifra; et al. (International Journal of Biometeorology, 2021)
The atmosphere is host to a complex electric environment, ranging from a global electric circuit generating fluctuating atmospheric electric fields to local lightning strikes and ions. While research on interactions of organisms with their electrical environment is deeply rooted in the aquatic environment, it has hitherto been confined to interactions with local electrical phenomena and organismal perception of electric fields. However, there is emerging evidence of coupling between large- and small-scale atmospheric electrical phenomena and various biological processes in terrestrial environments that even appear to be tied to continental waters. Here, we synthesize our current understanding of this connectivity, discussing how atmospheric electricity can affect various levels of biological organization across multiple ecosystems. We identify opportunities for research, highlighting its complexity and interdisciplinary nature and draw attention to both conceptual and technical challenges lying ahead of our future understanding of the relationship between atmospheric electricity and the organization and functioning of biological systems.